Diabetes Mellitus Preventive Behaviour in The Sibela Community Health Center; Determinant Factor - Wijayanti, Anisa Catur; Kusuma Estu Werdani; Arifa, Nida Dwi; Hidayah, Avifah Ainun; Puspita, Widya Galih (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Diabetes Mellitus (DM) is a severe problem in the world and Indonesia. The prevalence of DM at Sibela Community Health Center in Surakarta City in 2021 was 3.37%, the highest in Surakarta City. Efforts are needed to prevent DM through behavioral interventions. Several factors influence DM prevention behavior, such as family history, family support, knowledge, and attitudes. Methods: The independent variables in this study include family history, family support, knowledge, and attitude. This study is an analytic observational study with a cross-sectional approach. The population of this study were people who lived in the Sibela Health Center Working Area and did not suffer from DM. The sample in this study was 167 respondents, with a sampling technique using purposive sampling. The research instrument used a questionnaire with data collection techniques in the form of interviews. Data analysis used logistic regression with a confidence level of 95% and a significance level of ? = 0.05. Results: The results showed that there was a relationship between attitude and DM prevention behavior (p-value = 0.016), and there was no relationship between family history (p-value = 0.719), family support (p-value = 0.131), and knowledge (p-value = 0.815) with DM prevention behavior. Conclusion: Attitude is one of the determinant factors related to DM preventive behavior, it is hoped that the POSBINDU PTM can be implemented more broadly and comprehensively through the program, such as developing a physical agenda, training to improve skills such as meal planning, exercise, and stress management, training cadres on skills, and providing remote health access.